Chemical Comparison of Monk Fruit Products Processed by Different Drying Methods Using High-Performance Thin-Layer Chromatography Combined With Chemometric Analysis - Hong, Hui-Jie; Yang, Qi; Liu, Qiao; Leong, Fong; Chen, Xiao-Jia (Frontiers in Nutrition, 2022)
Monk fruit, also named Luohanguo, is the fruit of Siraitia grosvenorii (Swingle) C. Jeffrey ex A. M. Lu et Z. Y. Zhang and has been used as both food and traditional Chinese medicine. Monk fruit is usually processed by hot-air drying or using low temperature techniques after harvest due to preservation concern. In this study, high performance thin layer chromatography (HPTLC) method was developed for the analysis of 13 mogrosides, 1 flavonoid and 3 sugars in monk fruit products. Then chemometric analysis was applied to investigate the chemical characteristics in the samples dried by different methods. The results showed that the contents of mogroside V, 11-oxo-mogroside V, isomogroside V and sucrose in monk fruits dried at low temperature were much higher than those in traditional hot-air drying samples, which was also confirmed by HPTLC-scanning. These findings indicate that HPTLC combined with chemometric analysis provide a reliable tool to understand the chemical differences between the monk fruit products processed by different drying methods, which will be helpful for their quality evaluation.